Peptidic Activity Based Probes to Understand the Deubiquitination Machinery - Cataldi, Valerio (Trinity College Dublin. School of Chemistry. Discipline of Chemistry, 2025)
Ubiquitination is a highly conserved post-translational modification (PTM) that governs numerous critical cellular events such as protein degradation and membrane import/export. Such process is tightly regulated by a complex enzymatic network. Deubiquitinating enzymes (DUBs) are a group of isopeptidases that remove ubiquitin from their target proteins, providing a further control point for protein ubiquitination. Eukaryotes express over 100 DUBs, and the dysregulation of these enzymes has been linked to several diseases, including but not limited to cancer and neurogenerative disorders. Activity Based Probes (ABPs) have emerged as useful tools to understand DUBs and unravel their mechanism of action. Typically, ABPs targeting DUBs are designed on either a mono- or multi-ubiquitin scaffold and include an electrophilic moiety that is positioned to come in close proximity to the active site cysteine, enabling covalent interaction with the targeted DUB. While these probes remarkably advanced the mechanistic and structural understanding of DUBs, they suffer from onerous synthesis. This work aims to develop a new strategy to study DUBs with previously unexplored peptidic ABPs. Such novel peptide-based probes were designed, synthesised and their activity was tested against DUBs. The first set of peptide probes was designed to capture the DUBs removing ubiquitin from the p53 protein. p53 is a highly versatile transcription factor; its activity is modulated by different PTMs. In healthy cells, ubiquitination and subsequent degradation by the proteasome keep p53 basal levels low. However, following stress or DNA damage p53 is saved from proteasomal degradation by DUBs, triggering a stress-specific response. With respect to p53, nearly 15 DUBs have been reported to interact with p53, either as positive or negative regulators. However, the DUB (or set of DUBs) responsible for deubiquitination at recently discovered K291/K292 sites has not yet been characterized. In a section of this study, ABPs were generated using a portion of the p53 sequence that was synthetically modified to incorporate different electrophilic moieties. Being designed to target p53 deubiquitination only, this approach identified new functions of DUB enzymes and broadened our knowledge on p53 PTMs. The second set of peptide probes was designed to covalently label OTUB1, a highly specific DUB responsible for cleavage of K48 polyubiquitin chains. In a section of this work, a set of peptide probes was designed and synthesised, and their labelling activity towards OTUB1 was evaluated. Overall, this work outlines a novel strategy for targeting deubiquitinating enzymes using peptidic Activity Based Probes. While these probes were not specifically designed to outperform existing DUB-targeting probes, they represent the first attempt to incorporate peptide chemistry into ABPs design for DUB targeting.
APPROVED